PENGARUH EFEKTIVITAS ASET, NPM, DAN ROE TERHADAP KAPITALISASI PASAR SUB SEKTOR PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA (TAHUN 2012-2021) - Nurul Khamidah; Aliffia Nur Fauziah; Natasya Rahmawati Putri (Nusantara Hasana Journal, 2023)
This research is entitled "The Effect of Asset Effectiveness, Net Profit Margin, and Return on Equity on Market Capitalization (Conventional Banking Sub-Sector Listed on the Indonesia Stock Exchange in 2012-2021)". This study aims to determine the effect of asset effectiveness, net profit margin, and return on equity on market capitalization in the banking sub-sector listed on the Indonesia Stock Exchange in 2012-2021. This research method uses multiple linear regression analysis with the processing of Econometric Views 10 program tools. The sampling method of this research uses purposive sampling method. The results of the study show that asset effectiveness has a positive effect on market capitalization. NPM and ROE have a negative effect on market capitalization. For companies, the value of market capitalization is very important because it reflects the total company, the greater the market capitalization, the higher the company will be valued by the market. The size of the market capitalization for shareholders affects the value of shareholder wealth. The higher the company's share capitalization, the greater the shareholder value.